Serum BNP levels are associated with malignant pericardial effusion. (June 2019) - Carasso, Shemy; Grosman-Rimon, Liza; Nassar, Ali; Kusniec, Fabio; Ghanim, Diab; Elbaz-Greener, Gabby; Kinany, Wadi; Sudarsky, Doron; Hazanov, Evgeni; Amir, Offer
Abstract: Introduction: The development of malignant pericardial effusion indicates a poor prognosis and is the leading cause of cardiac tamponade. The objectives of the study were to examine the levels of BNP in traumatic, malignant and non-malignant pericardial effusion etiologies, and to assess the value of serum and pericardial fluid BNP levels in the prognosis of malignant pericardial effusion. Methods: A of 56 patients with clinical and echocardiographic diagnosis of pre-tamponade or tamponade who required pericardiocentesis were included in the study. BNP levels were assessed in the serum and within the pericardial fluid. The diagnostic value of BNP levels in discriminating between malignant and non- malignant etiology of pericardial effusion was examined using a receiver-operating characteristic (ROC). Results: Pericardial fluid BNP levels were similar across all etiology groups. In patients with malignant etiology, the amount of pericardial fluid was high and their serum BNP levels were relatively low. BNP levels were strong predictors of malignant pericardial effusion, and the cut-off point of BNP ≤ 250 pg/ml demonstrated the highest sensitivity (90.0%) for malignant etiology. Conclusions: Low serum BNP levels were significantly associated with malignancy in patients undergoing pericardiocentesis for pericardial effusions. Serum BNP levels <250 pg/ml may trigger more extensive diagnostic testing for malignant pericardial effusion in patients with small pericardial effusion who are not considered for pericardiocentesis due to small effusion, in whom the etiology is unclear.